2021
DOI: 10.15587/1729-4061.2021.238440
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for determining the thermoelastic state of a reinforced concrete bridge beam strengthened with methyl methacrylate

Abstract: This paper reports the analysis of methods for determining temperature stresses and deformations in bridge structures under the influence of climatic temperature changes in the environment. A one-dimensional model has been applied to determine the temperature field and thermoelastic state in order to practically estimate the temperature fields and stresses of strengthened beams taking into consideration temperature changes in the environment. The temperature field distribution has been determined in the vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The study of the temperature field in a three-layer model (defective ferroconcrete pipe reinforced with a metal corrugated structure) [20] has established the nonuniformity of temperature distribution across the layers, which leads to a contact effect defined by non-ideal conditions of heat exchange at the junction between the layers. Similar calculation outcomes of temperature fields have been achieved in the studies on multilayered bridge structures [21,22].…”
Section: Literature Reviewsupporting
confidence: 73%
See 1 more Smart Citation
“…The study of the temperature field in a three-layer model (defective ferroconcrete pipe reinforced with a metal corrugated structure) [20] has established the nonuniformity of temperature distribution across the layers, which leads to a contact effect defined by non-ideal conditions of heat exchange at the junction between the layers. Similar calculation outcomes of temperature fields have been achieved in the studies on multilayered bridge structures [21,22].…”
Section: Literature Reviewsupporting
confidence: 73%
“…These papers mainly deal with the heating of the solid through the coating, with the issues of head conduction over the coating and exchange of heat with the solid and the ambient environment not being elaborated on. Papers [20][21][22] present temperature distributions in piecewise inhomogeneous solids and estimate their impact on the strength of structural elements. The study of the temperature field in a three-layer model (defective ferroconcrete pipe reinforced with a metal corrugated structure) [20] has established the nonuniformity of temperature distribution across the layers, which leads to a contact effect defined by non-ideal conditions of heat exchange at the junction between the layers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The issue of the use of polymeric materials is relevant to increase the bearing capacity of transport structures. In [16], the results of the assessment of the thermally-stressed state of reinforced concrete bridge beams restored by methyl methacrylate polymers are reported. As a result, it was found that the strength of the restored beams increases.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…From the review of works [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] it follows that the assessment of the residual resource of asphalt pavement on reinforced concrete road bridges, taking into account the influence of temperature factors with the influence of time and the action of transport load, is a necessary and urgent task of scientific research. It is also necessary to devise a unified methodological basis for a comprehensive method for calculating the residual life of asphalt concrete pavement using SBR polymers on reinforced concrete road bridges, taking into account the joint effect of temperature (seasonal annual and daily temperatures) and vehicles.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%